Integrating MOOCs into traditional higher education modules: a MOOC-based blend framework - Karla K. de Lima Guedes; Hugh C. Davis; John Schulz (Association for Learning Technology, 2022)
Online learning platforms, such as MOOCs (Massive Open Online Courses), continue to expand, and some academics are taking advantage of these resources by integrating them into their teaching. The literature shows that there are many different ways that MOOCS are being blended into on-campus university teaching, and it would be helpful to have a framework that demonstrates the relationship between the in-person and MOOC curricula content, and the Blended Learning models used in practice. This study investigated how some UK academics are blending MOOCs into their in-person teaching and whether the blends used had any impact on course design. Semi-structured interviews were conducted with six participants with MOOC blending experience, and data were analysed using an inductive approach to Thematic Analysis. Results from this study generated an understanding of (1) what parts of MOOCs lecturers are using and how these resources are being blended into their in-person courses, (2) what kind of impact a MOOC-based blend can have on a course design and (3) the MOOC-based blend framework - a framework to assess the extent to which readily available MOOCs are integrated into lecture-based university modules in terms of curricular alignment and types of blend.